Research on Curricular Development for Pre-Kindergarten Mathematics and Science. Issue 7 (July 2015) - Kinzie, Mable B.; Whittaker, Jessica Vick; Mcguire, Pat; Lee, Youngju; Kilday, Carolyn
Background/Context: As increasing attention is paid to preparing students to succeed in school, the development and adoption of research-based curricula have become progressively more important. However, many curricular designs lack a basis in scientific evidence; research and curricular design are frequently treated as two separate enterprises. Purpose/Objective: In this paper, we present the Research on Curriculum Design (RCD) model, first advanced by Clements in 2007, with results from its application to the design and iterative development of pre-kindergarten mathematics and science curricula. Research Design: RCD is an example of design-based research, with the additional specific goals of the production of an effective curriculum and the evolution of theoretical guidelines to inform future curricular designs. Our implementation spanned two years and involved iterative development and testing of two, year-long curricula. Findings/Results: Application of RCD methods informed our understandings of the target population, the knowledge and skills to be developed, and the theoretical and research-based models that guided the designs. Subsequent iterative development and evaluation in five pre-K classrooms enabled refinement of the curricular design, as well as the evolution of design guidelines useful for informing future curriculum development efforts. A culminating test of the resulting curricula in eight pre-K classrooms suggests the success of the RCD approach, yielding high-quality, high-fidelity teacher implementation, with teacher fidelity and curricular dosage predicting students' mathematics learning gains across the year. Conclusions/Recommendations: Results support the value of the RCD model for achieving research-based curricula that have the potential to effectively support teachers in their practice and positively impact children's early learning.